2000
DOI: 10.1093/hmg/9.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in the candidate tumor suppressor gene Hic1 exhibit developmental defects of structures affected in the Miller-Dieker syndrome

Abstract: HIC1 is a candidate tumor suppressor gene which is frequently hypermethylated in human tumors, and its location within the Miller-Dieker syndrome's critical deletion region at chromosome 17p13.3 makes it a candidate gene for involvement in this gene deletion syndrome. To study the function of murine Hic1 in development, we have created Hic1 -deficient mice. These animals die perinatally and exhibit varying combinations of gross developmental defects throughout the second half of development, including acrania,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 32 publications
2
78
0
2
Order By: Relevance
“…P57KIP2 is the only CIP/KIP gene whose targeted disruption results in developmental abnormalities, leading to death soon after birth (67). Thus, in addition to its role in cell cycle regulation, P57KIP2 is essential for normal development, exactly as HIC1 since homozygous Hic1 Ϫ/Ϫ mouse embryos display severe developmental defects culminating in perinatal death (6). The repression of P57KIP2 that we observed between quiescent and growing fibroblasts could thus be only partially related to cell cycle regulation but also to a yet-unidentified developmental process.…”
Section: Discussionmentioning
confidence: 99%
“…P57KIP2 is the only CIP/KIP gene whose targeted disruption results in developmental abnormalities, leading to death soon after birth (67). Thus, in addition to its role in cell cycle regulation, P57KIP2 is essential for normal development, exactly as HIC1 since homozygous Hic1 Ϫ/Ϫ mouse embryos display severe developmental defects culminating in perinatal death (6). The repression of P57KIP2 that we observed between quiescent and growing fibroblasts could thus be only partially related to cell cycle regulation but also to a yet-unidentified developmental process.…”
Section: Discussionmentioning
confidence: 99%
“…Other transcription factors found in the cluster were recognized as being functionally involved in several complex developmental processes. This is the case for NFI/A, which is expressed in a wide variety of embryonic and adult tissues (Chaudhry et al, 1997); NFI/B, which is implicated in normal lung development (Grunder et al, 2002); Hic-1, a candidate tumor suppressor gene, whose ablation produces the developmental defects observed in the Miller-Dieker syndrome (acrania, exencephaly, cleft palate, limb abnormalities and omphalocele) (Carter et al, 2000); Peg3/Pw1, a zinc finger containing protein, shown to be a necessary participant of p53-mediated apoptosis in fibroblasts (Relaix et al, 2000) and neurons (Deng and Wu, Journal of Cell Science 117 (19) …”
Section: Gene Profile Of Mesoangioblastsmentioning
confidence: 99%
“…Although homozygous disruption of HIC1 impairs development and leads to embryonic and perinatal lethality (11), mice with heterozygous HIC1 inactivation (Hic1 þ/À ) have the propensity to form spontaneous tumors (12). The presence of HIC1 silence is associated with preneoplastic conditions such as smoker's lung, colonic polyps, and cirrhotic liver (13).…”
Section: Introductionmentioning
confidence: 99%